2007
DOI: 10.1176/ajp.2007.164.1.160
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Aripiprazole, Methylphenidate, and Placebo for Amphetamine Dependence

Abstract: Methylphenidate is an effective treatment for reducing intravenous drug use in patients with severe amphetamine dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
109
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 6 publications
8
109
2
Order By: Relevance
“…However, a recent clinical trial for amphetamine dependence was terminated early because the aripiprazole group showed greater amphetamine use than those receiving placebo (Tiihonen et al 2007), which appears consistent with the human laboratory findings with cocaine.…”
Section: Clinical Trialmentioning
confidence: 60%
“…However, a recent clinical trial for amphetamine dependence was terminated early because the aripiprazole group showed greater amphetamine use than those receiving placebo (Tiihonen et al 2007), which appears consistent with the human laboratory findings with cocaine.…”
Section: Clinical Trialmentioning
confidence: 60%
“…Preclinical data suggest that methylphenidate is capable of attenuating the effects of high doses of methamphetamine on the DA transporter (Sandoval et al, 2003). Indeed, early pilot clinical data on methylphenidate in heavy users of intravenous amphetamines showed promising results in reducing their amphetamine use (Tiihonen et al, 2007). Data from the interim analysis of a trial of D-amphetamine in Australia suggest that it may be beneficial for methamphetaminedependent patients (Wickes et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Grabowski and colleagues suggested that because methylphenidate had more peripheral than central nervous system effects, it may not have been an adequate reinforcer for cocaine. A recent study compared methylphenidate (54 mg/day sustained release), aripiprazole (a novel partial dopamine receptor agonist) and placebo in dependent amphetamine injectors [62]. The study was terminated early, as the aripiprazole study arm had significantly worse outcomes than the placebo arm.…”
Section: Indirect Dopamine Agonists For Psychostimulant Dependencementioning
confidence: 99%